Assessing Trogodermavariabileas a behavioral surrogate for the quarantine pest, Trogodermagranarium(Coleoptera: Dermestidae), through dual choice assays - Grosdidier, Robert; Morrison, William R.; Arthur, Frank; Domingue, Michael (My University, 2017)
Stored product pests are a leading cause of post harvest losses in nations around the world, accounting for up to 20% of losses in some developing nations. The Khapra beetle (or KB), Trogoderma granarium(Fig. 1A), is a threat to the biosecurity of the U.S., and represents the only stored product species under quarantine in the country. In the past several years, there has been an increasing frequency of T. granariumat ports of entry and borders in the U.S. Because researchers can only work with the pest in quarantine, research on T. granariumis necessarily limited because only a handful of facilities have permission to keep colonies of the species. The closely related beetle, Trogoderma variabile (the warehouse beetle or WHB; Fig. 1B) is commonly present throughout stored product facilities in the U.S., causes economic losses (Fig. 2A),and is not under quarantine. Due to physical similarities (Fig. 1), and their close relatedness, it is possible that their behavioral responses are also similar. This raises the question of whether one can act as a behavioral surrogate for the other, which would speed research into how T. granarium would respond to stimuli if it gained entry in the U.S.